2018
DOI: 10.3389/fpsyg.2018.01103
|View full text |Cite
|
Sign up to set email alerts
|

Does SMS-Support Make a Difference? Effectiveness of a Two-Week Online-Training to Overcome Procrastination. A Randomized Controlled Trial

Abstract: The primary purpose of this randomized controlled trial (RCT) was to evaluate the efficacy of an unguided, 2-week internet-based training program to overcome procrastination, called ON.TOP. Because adherence is a typical problem among individuals who tend to procrastinate, especially with internet-based interventions, the secondary purpose of the present study was to investigate whether adding SMS support increases subjects’ frequency of engagement in training. In a three-armed RCT (N = 161), the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 93 publications
(114 reference statements)
1
24
0
Order By: Relevance
“…Even though automatic reminders were sent if the participant did not continue with the next module, a more intensive and probably also more personal reminding strategy might be indicated to overcome time-management and motivational problems. Elaborate strategies like sending of reminder e-mails based on participant-behavior as well as on course timeline ( Titov et al, 2013 ), regular telephone coaching focused on adherence ( Mohr et al, 2013 ) or implementation of an SMS coach ( Eckert et al, 2018 ) have already been shown to substantially increase intervention adherence. Indeed, previous studies evaluating effectiveness of GET.ON Mood Enhancer, Mood Enhancer Diabetes and GET.ON Stress observing high rates of intervention adherence and effectiveness already implemented a SMS coach ( Buntrock et al, 2016 , Buntrock et al, 2015 ; Ebert et al, 2017b ; Heber et al, 2016 ; Nobis et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though automatic reminders were sent if the participant did not continue with the next module, a more intensive and probably also more personal reminding strategy might be indicated to overcome time-management and motivational problems. Elaborate strategies like sending of reminder e-mails based on participant-behavior as well as on course timeline ( Titov et al, 2013 ), regular telephone coaching focused on adherence ( Mohr et al, 2013 ) or implementation of an SMS coach ( Eckert et al, 2018 ) have already been shown to substantially increase intervention adherence. Indeed, previous studies evaluating effectiveness of GET.ON Mood Enhancer, Mood Enhancer Diabetes and GET.ON Stress observing high rates of intervention adherence and effectiveness already implemented a SMS coach ( Buntrock et al, 2016 , Buntrock et al, 2015 ; Ebert et al, 2017b ; Heber et al, 2016 ; Nobis et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous trials have demonstrated an augmenting effect of text messages on the efficacy of and adherence to IBIs (Eckert et al, 2018).…”
Section: Internet-based Cbt For Somatic Symptom Distressmentioning
confidence: 98%
“…Therefore, we have set a control group comparison of this randomized controlled trial, that 36 days after completing the initial evaluation, will receive the intervention and also preventive measures considered to prevent damage to the participants and previously provide explanations. Finally, regarding this limitation, articles with well-designed studies were also considered, as well as recent articles published in prestigious journals that included a wait list control group for Online or presential Psychological Interventions (Eckert et al, 2018 ; Hjemdal et al, 2019 ; Stächele et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%